Business associations, access to finance, and institutional quality: Drivers of SMEs’ circular economy transformation - Sánchez-Teba, Eva María; González-Fernández, Ana Isabel; Bermúdez-González, Guillermo José (Taylor & Francis, 2025)
This paper examines how small and medium-sized enterprises (SMEs) engage in the circular economy (CE) through business association (BA) membership, perceptions of ease access to finance (AF), and institutional quality (IQ). Building on social capital theory, we argue that BA membership not only provides resources but also channels non-financial forms of public entrepreneurship and SME-supporting policies. Framed through a theory of change perspective, these soft interventions enhance social and human capital, enabling CE adoption. Using Eurobarometer 486 data from 7,680 SMEs in 39 countries, logit and OLS regressions show that BA membership fosters CE actions while increasing awareness of financial barriers, with AF partially mediating this link. IQ moderates these dynamics: in high-IQ contexts, non-financial support reduces the salience of financial barriers; in low-IQ contexts, AF perceptions remain decisive. We contribute by integrating SCT with public entrepreneurship to explain policy conditions shaping SME sustainability.
Keywords: Economía circular; Pequeñas y medianas empresas; SME; Circular economy; Business association; Access to finance; Institutional quality; Social capital theory